Incomprehensible Concepts and Contexts: Teaching The Duchess of Malfi in Bhutan - Kuruvella, Babu Shankar Rao (Radical Teacher, 2023)
Teaching a Jacobean British text such as The Duchess of Malfi by John Webster to the Bhutanese students was a real challenge as the text deals with a world of class and gender hierarchy. Living in a Buddhist country, where even the killing of animals for food is prohibited and the Gross National Happiness is prioritized, the psychological trauma and the violent and gory events portrayed in the play appalled the students. The students could not imagine a world of female subjugation, gory, and bloodshed. Therefore, the teacher takes caste and community-based honor killing contemporary examples from their neighboring country, India, to explicate the world of the Duchess. Thus, they could understand a culturally different text via examples from India.